How to consolidate business presence in foreign markets? considerations about the internationalization process - Scherer, Flavia Luciane (Revista de Administração da UFSM, 2012)
This theoretical article aims to raise considerations regarding the internationalization of companies, with emphasis on issues underlying the maintenance and growth of its operations in foreign markets. In the academic environment, was quickly perceived that increased globalization has led to new perspectives in terms of companies' performance in a context of high competition. This movement propelled the growing interest in the study of the phenomenon of globalization and the processes involved in the management of companies operating in foreign markets. In this article, we proceeded to the presentation of approaches to the study of internationalization, which led to the conclusion that the studies referenced - in the fields of organizational theory and marketing / international business - do not present theoretical constructs that allow the invetigation of the consolidation as the final step in the internationalization process. It seems to be the timely pursuit of variables and indicators that lead to proper characterization and analysis of this period. Understand how companies remained working abroad, profitably, can generate useful insighst to planning for stimulus to internationalization, as well as providing the necessary advancement of the body of theoretical knowledge about the subject.